PEMBATALAN MEREK DITINJAU DARI UNDANG-UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS (STUDI KASUS PUTUSAN KASASI NOMOR 375 K/PDT.SUS.HKI/2020) - Naim, Putri; Ismi, Hayatul; Dasrol, Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The era of global trade can be maintained if there is a healthy business competition climate. Currently, more and more entrepreneurs are competing in producing their respective products, both middle and upper-middle entrepreneurs. Entrepreneurs produce the best possible products because they can see that most Indonesians prefer good and guaranteed quality. In terms of food needs, people usually choose products according to their tastes, for reasons of health and guaranteed taste. To distinguish one product from another, it can be distinguished by the presence of a brand. The purpose of writing this thesis: First, to find out the cancellation of the trademark regulated in Law Number 20 of 2016 concerning Marks and Geographical Indications. Second, to find out the reasons for the judge in canceling the